Optimization problem with interval-valued random functions (2012)
This paper proposes optimization with interval-valued random functions as a very natural theoretical tool for posing and solving optimization problems arising in various fields such as oil reservoir exploration and structural design, since the input data for these problems consist of large sets of inequalities, obtained by repeating a particular measurement many times. The technique of weighted sums, the Aumann’s integral and properties of interval arithmetic are used to establish necessary and sufficient conditions for the solution of these optimization problems. Moreover, we compare the numerical results obtained by applying the stochastic approach and the interval approach.